The Physical Workload of Surgeons: A Comparison of SILS and Conventional Laparoscopy. (August 2015) - Alleblas, Chantal C. J.; Velthuis, Simone; Nieboer, Theodoor E.; Sietses, Colin; Stegeman, Dick F.
Background. As extensively reported in the literature, laparoscopic surgery has many advantages for the patient. Surgeons, however, experience increased physical burden when laparoscopic surgery is compared with open surgery. Single-incision laparoscopic surgery (SILS) has been said to further enhance the patient's benefits of endoscopic surgery. Because in this surgical technique only 1 incision is made instead of the 3 to 5, as in conventional laparoscopic surgery (CLS), it is claimed to further reduce discomfort and pain in patients. Yet little is known about its impact on surgeons. This study aims to contribute by indicating the possible differences in physical workload between single-incision laparoscopy and CLS. Methods. A laparoscopic box trainer was used to simulate a surgical setting. Participants performed 2 series of 3 different tasks in the box: one in the conventional way, the other through SILS. Surface electromyography was recorded from 8 muscles bilaterally. Furthermore, questionnaires on perceived workload were completed. Results. Differences were found in the back, neck, and shoulder muscles, with significantly higher muscle activity in the musculus (M) longissimus, M trapezius pars descendens, and the M deltoideus pars clavicularis. Questionnaires did not indicate any significant differences in perceived workload. Conclusion. Performing SILS versus CLS increases the objectively measured physical workload of surgeons particularly in the back, neck, and shoulder muscles.